Commercial Banks Versus BPR: Advantages Based On Perception, Hope And Customer Interest - Budiwati, Hesti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2017)
Commercial banks and Bank Perkreditan Rakyat are two different types of banks whose existence in society aims to raise and channel public funds to improve people's lives. The facts show that there is a sharp competition between the two types of banks in terms of gaining public trust to become bank customer but although these two types of banks are different but still able to develop well in society. This study aims to identify the factors that become competitive advantage at Commercial Banks and Bank Perkreditan Rakyat from the customer's point of view based on customers' perceptions, expectations and interests so banks can determine competitive strategy. The approach used in this research is Lean Six Sigma approach with a sample of 60 respondents consisting of 30 customers of Commercial Banks and 30 customers of Bank Perkreditan Rakyat. Respondents will be asked to respond to research instruments based on their perceptions, expectations and interests. The results of the study there are five competitive advantages in Commercial Banks (1) promotions made, (2) reward appeal, (3) saving security, (4) cleanliness and comfort of the room, (5) friendliness, courtesy and neatness. Bank Perkreditan Rakyat obtained competitive advantage that is (1) cleanliness and comfort of the room,(2) ability and alertness of the officers, (3) friendliness, courtesy and neatness, (4) saving security, (5) familiarity of the officer with the customer. In addition there are similarities there are interesting differences that is on the excellence of promotional activities and the attractiveness of prizes at Commercial Banks. and the familiarity of officers with customers at Bank Perkreditan Rakyat.